2017
DOI: 10.1122/1.4982701
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization mechanism induced by organoclay in PMMA/PS blends

Abstract: In this work, the effect of adding organoclay (Cloisite 20A) to a poly(methyl metacrylate) (PMMA)/polystyrene (PS) blend was evaluated in order to understand the compatibilization mechanism taking place. The blend morphology was quantified using micrographs obtained by scanning electron microscopy and observed by transmission electron microscopy. The state of dispersion of the clay was studied using small angle X-ray scattering and wide angle X-ray scattering and by applying the Carreau-Yasuda with a yield str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…5, the interfacial tension of each blend can be calculated. The interfacial tension between PMMA and PS can be found in the literature to be between 1 and 3 mN/m [8,15,29,31]. The values found here are of the same orders of magnitude, which decrease with the addition of BC1 but increase with the addition of BC2 (see Table III).…”
Section: B Interfacial Tension and Marangoni Stressessupporting
confidence: 75%
See 2 more Smart Citations
“…5, the interfacial tension of each blend can be calculated. The interfacial tension between PMMA and PS can be found in the literature to be between 1 and 3 mN/m [8,15,29,31]. The values found here are of the same orders of magnitude, which decrease with the addition of BC1 but increase with the addition of BC2 (see Table III).…”
Section: B Interfacial Tension and Marangoni Stressessupporting
confidence: 75%
“…5(c). To verify this assumption, other rheological measurements were conducted at lower temperature: As already shown by Genoyer et al [29], Marangoni's relaxation is influenced by temperature. By decreasing the temperature, the movements of BCs at the interface will be longer as the viscosity increases.…”
Section: B Interfacial Tension and Marangoni Stressesmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, in many cases, the incorporation of particles in the blends and their selective localization often induces changes in the blend's morphology. In particular, their localization at the interface effectively suppresses coarsening and promotes refined and stable blend morphologies [27,29,[41][42][43][44][45]. In the same context, it was found that plate-like fillers, among them graphene, can adapt better to polymer-polymer interfaces and are subsequently more efficient in suppressing coarsening [42].…”
Section: Introductionmentioning
confidence: 94%
“…Generally, upon addition of a compatibilizer and irrespective of its chemical nature, one or several of the following phenomena can be observed in the case of a blend with a droplet dispersion type morphology: reduction of the droplet size [21], [22], inhibition of droplet's coalescence [23]- [27], decrease in interfacial tension [28]- [32], and presence of an additional relaxation phenomenon [28], [32]- [40]. The additional relaxation phenomenon observed upon addition of compatibilizers is known to correspond to the relaxation of Marangoni stresses induced by a non-homogeneous concentration of compatibilizers at the interface [34], [39]- [41].…”
Section: Introductionmentioning
confidence: 99%